DINAMIKA DIGITALISASI DAN KONVERGENSI INDUSTRI MEDIA (Studi Kasus Pada Aplikasi Vision+ Oleh MNC Group) - Sajdahfath, Tiyo; Putra, Afdal Makkuraga; Jamil, Achmad (MediaKom : Jurnal Ilmiah Komunikasi, 2024)
With the presence of internet technology bringing the trend of media convergence movement, it makes some media begin to adapt to the current technological shift and shift from conventional media to convergence media. Media convergence has caused various mass media companies to start innovating, including MNC Group as one of the leading media companies in Indonesia. One form of convergence carried out by MNC Group is by releasing the Vision+ application which is a digital streaming media service for live TV and Video On Demand (VOD) owned by MNC Group. The author is interested in observing the phenomenon of digitalization and convergence in the media industry. This research uses a constructivist paradigm with a qualitative approach and this research method uses case studies. The results showed that the media convergence process on the Vision+ application owned by MNC Group succeeded gradually by showing convergence levels including ownership convergence, tactical convergence, structural convergence, storytelling convergence. MNC Group's opportunities in the transition of conventional media to digital through the Vision+ application, including trends and increasing public needs for digital-based entertainment content, a large and varied content that is an advantage for Vision+ to excel from its competitors. The challenges faced by Vision+ include competition that raises competitors with similar media products, as well as changes in the media business environment and the development of digital technology that creates various other digital media options from OTT applications such as Vision+.